Unravelling nitric oxide–hydrogen sulfide interplay in NaCl-mediated salinity resistance of moth bean [Vigna aconitifolia (Jacq.) Marechal] - Kumud, Gaur; Kamakshi, Saxena; Yogendra Prasad, Saksena; Sheetal; Bharti, Kaushik; Dwaipayan, Sinha; Arun Kumar, Mauya (Plant Science Today, 2025)
Soil salinity causes oxidative stress, ion imbalance, osmotic anomaly, nutrient imbalance, and changes in plant growth regulators. The study aims to investigate the salinity tolerance limit, involvement of nitric oxide (NO) and hydrogen sulfide (H2S), and effects of different concentrations of exogenously supplied sodium chloride (NaCl) (50, 100, 150, 200, and 250 mM) on growth, physiological and biochemical parameters of the Moth bean [Vigna aconitifolia (Jacq.) Marechal] seedlings. Moth bean, a neglected and underutilised legume crop in India. The experimental results showed that salinity led to decrease in the plant growth [64.8% shoot length (SL), 58.6% root length (RL), 97.5% secondary roots], 19.3% fresh weight (FW), 16.01% dry weight (DW), (25.6%) water content, photosynthetic pigments (58.2% chl a, 20% chl b, 47.7% total chl, and 63.9% carotenoids), 27.3% antioxidant contents, and 23.7% increased malondialdehyde (MDA) content. The endogenous generation of NO (4.9%) and H2S (58%) were reported under salinity stress compared to the control treatment. The osmolyte proline (184.2%) and enhanced activities of antioxidant enzymes, such as catalase (CAT) (25.22%), peroxidase (POD) (22.25%), superoxide dismutase (SOD) (17.63%), and polyphenol oxidase (PPO) (24.80%), up to 150 mM NaCl treatment, marking the tolerance limit of the moth bean. Principal component analysis (PCA) and correlation analysis revealed the antagonistic generation pattern of NO and H2S, as well as their relationships with antioxidant enzymes under stress conditions. This is the first report on NO and H2S generation and involvement in Moth bean grown under salinity stress. The information obtained can be applied to augment salinity stress and enhance crop productivity.